Social capital and income generation in South Africa, 1993-98 - Maluccio, John; Haddad, Lawrence James; May, Julian (International Food Policy Research Institute, 1999)
The goal of this paper is to determine the nature of the causal relationship between social capital, as measured by household membership in formal and informal groups and household welfare in South Africa. Using a recently collected panel data set in South Africa's largest province, we estimate per capita expenditure functions and find a positive and significant impact of household-level social capital. For example, after controlling for fixed effects, social capital has no impact on per capita expenditure in 1993 but positive and significant effects in 1998. We interpret this as reflecting structural changes in the South African economy as it removes the many restrictions that underlay apartheid.